2016
DOI: 10.1111/1750-3841.13249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pleurotus eryngii Mushroom β‐Glucan on Quality Characteristics of Common Wheat Pasta

Abstract: The objective of this study was to evaluate the effect of β-glucan-rich fractions (BGRFs) from Pleurotus eryngii mushroom powder on the quality, textural properties, and sensory evaluation of common wheat pasta. Pasta was prepared from semolina flour and common wheat flour by replacing common wheat flour at 2%, 4%, and 6% with BGRFs. Semolina flour showed significantly higher viscosities than common wheat flour samples. However, all viscosities, except the breakdown viscosity, were reduced with increasing perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…powder could affect the sensory properties of some cereal-based products (e.g., bread, biscuits, and pasta) but no studies have been performed trying to design a low energy-dense vegetable base product, which are always more requested on the market due to the increasing phenomenon of obesity (Proserpio et al, 2016). Recently, Kim, Lee, Heo, and Moon (2016) have proposed the application of the insoluble β-glucan fraction separated from mushroom powder in pasta.…”
Section: Discussionmentioning
confidence: 99%
“…powder could affect the sensory properties of some cereal-based products (e.g., bread, biscuits, and pasta) but no studies have been performed trying to design a low energy-dense vegetable base product, which are always more requested on the market due to the increasing phenomenon of obesity (Proserpio et al, 2016). Recently, Kim, Lee, Heo, and Moon (2016) have proposed the application of the insoluble β-glucan fraction separated from mushroom powder in pasta.…”
Section: Discussionmentioning
confidence: 99%
“…In pasta, insoluble dietary fibre separated from mushroom powder was added at levels of 2-6% of semolina to fortify the product with mushroom β-glucans (Table 7) (Kim et al, 2016). 17 The results of sensory evaluation showed that common wheat pasta obtained the lowest liking scores, while the acceptability increased with the addition of the insoluble β-glucan fraction. In particular, the sample with 2% of the β-glucan-rich fractions added to replace wheat flour was significantly preferred compared to the sample without supplementation.…”
Section: Food Applicationsmentioning
confidence: 98%
“…12 The total dietary fibre content found in various studies is in the range 10.58-56.99 g per 100 g of fruit body dry weight (d.w.) ( Table 1). 7,8,[13][14][15][16][17][18][19][20][21] The AOAC enzymatic gravimetric method is the most frequently used to determine dietary fibre contents in mushrooms. However, the presence in the residue of non-protein nitrogen (N) originating from chitin (which is generally not mentioned) impairs the calculation and could be one of the reasons for the different values found by various authors.…”
Section: Composition and Nutritional Valuementioning
confidence: 99%
See 2 more Smart Citations